Antidiarrhoeal Activity and Total Tannin Content of Ethanolic Leaf Extract of Codiaeum variegatum - Labu, Zubair Khalid; Laboni, Farhina Rahman; Mamun, Mir Md Abdullah Al; Howlader, Md Sariful Islam (Dhaka University Journal of Pharmaceutical Sciences, 2015)
The present study was designed to investigate the antidiarrhoeal activity and determine the total tannin content of the ethanolic extract of the leaves of Codiaeum variegatum (Family- Euphorbiaceae). The antidiarrhoeal activity was evaluated in castor oil-induced diarrhoea in mice and the total tannin content was determined by using the Folin-Coicalteu phenol reagent. The ethanolic extract of leaves of C. variegatum showed a positive effect on castor oil induced diarrhoea in mice. In the antidiarrhoeal assay the extract inhibited the mean number of defecation by 40.81% and 59.18% (p<0.01 & p<0.001) at 250 mg/kg and 500 mg/kg body weight, respectively. The latent period for the extract treated group was (p<0.01 & p<0.001) increased as compared to control group. The total tannin content was quite significant and high in ethanolic extract (241.41 mg/g of tannic acid equivalent). Phytochemical screenings of the leaf extract indicated the presence of carbohydrate (reducing sugars), gums, steroids, alkaloids and tannins. Therefore, the results of the present study provide the scientific basis for the traditional uses of this plant as remedy for diarrhea. Dhaka Univ. J. Pharm. Sci. 14(1): 87-90, 2015 (June)